Analysis of the Impact of Coal Mineacid Water on River Water Quality, Biota, and Human Health Around Mining - Triyanchy Afaz; Abdul Razak; Nurhasan Syah; Skunda Diliarosta; Mulya Gusman (Science and Environmental Journal for Postgraduate, 2023)
Acid Mine Drainage (AMD) or Acidic Acidic Drainage (AAT) is a type of water runoff that happens when certain sulfide minerals in rocks come in contact with water and oxygen, triggering an oxidation process that results in water with acidic properties. To understand more about this phenomenon, a literature review was conducted using relevant keywords on online information sources. The indicators used to measure the level of acidity in mine water include pH, metal concentration, Total Suspended Solid (TSS) or turbidity level, electrical conductivity, sulfate, and sulfuric acid content. High electrical conductivity in mine water usually indicates the presence of metals such as iron (Fe) and manganese (Mn). High levels of manganese (Mn) in water can cause health problems for humans. Moreover, an increase in the concentration of Fe can cause an increase in turbidity or TSS because iron metal can dissolve in air and form solid particles that can cause turbidity. To reduce acidity and environmental pollution, passive or active treatment techniques can be used to neutralize AMD.